Designing A Successful Islamic Investment Portfolio: A Conceptual, Practical, And Inspirational Guide For Muslim Investors - Rahmad Hidayat Lubis; Hasnawiyah Hasnawiyah; Riski Rahmadani; Maulana Muklis; Paisal Rahmat (Universitas Islam Darul 'ulum Lamongan, 2026)
This study aims to design an Islamic investment portfolio framework that is integrated with sustainability principles (ESG) and evaluate its effectiveness in achieving halal and sustainable investment goals. The method used is a qualitative approach with a literature study, namely reviewing literature from books, journals, official reports, and websites of institutions related to Islamic investment. The analysis is done descriptively and through content analysis to find patterns of meaning and main principles in the management of Islamic portfolios. The results showed that Islamic portfolios that combine Islamic screening, ESG principles, and diversification strategies are able to provide competitive investment returns while being in accordance with Islamic values. The combination of assets such as Islamic stocks, green sukuk, money market instruments, and halal alternatives support portfolio stability. In addition, the use of technology such as Islamic robo-advisors and periodic rebalancing strengthens the effectiveness of portfolio management. In conclusion, a structured and sustainable Islamic portfolio can be a strategic solution for Muslim investors. It is recommended that Islamic financial literacy continues to be improved, ESG integration is expanded in Islamic products, and digital technology is strengthened to create an inclusive and competitive investment ecosystem.